Peningkatan Kualitas Sdm Bagi Karang Taruna di Wisata Kampung Kelengkeng Desa Simoketawang, Kecamatan Wonoayu, Kabupaten Sidoarjo - Arga Christian Sitohang; Febby Rahmatullah Masruchin; Salvia Rahma; Maudy Priya; Rica N Halimatus; Candra Pramesti Lilabilah; Fitriana Dewi Silaen (Universitas Nahdlatul Ulama Surabaya, 2022)
The matching fund is a program that helps youth organizations in Simoketawang village to increase their economic productivity. Universitas 17 August 1945 or Untag Surabaya through the Matching Fund program seeks to connect the world through the business world in Simoketawang village. A real effort to equip new businesses in preparing youth content creators to enter the online world media so that they can help them create creative and interesting content. We will create media content in simoketawang village. We have trained them in product creation, innovation and design and also provided new ideas in their media content productivity so that they become reliable content creators in online social media. This matching fund activity is to improve the quality of youth human resources through content media products in Kelengkeng Simoketawang Tourism Village, Wonoayu District, Sidoarjo Regency. The method of implementing this activity is carried out collaboratively between the implementers of the Companion Fund program, the Community Empowerment & Village Development Agency, and is divided into three stages, namely preliminary surveys, training and marketing with target youth groups. The results of these activities include increasing practical knowledge that is easy to apply in production for the creation of media content on social media content. In this training, youth organizations know how to create media content properly and in accordance with social media rules in publications. The youth organizations are very enthusiastic and enthusiastic in supporting the program in the longan tourism village and participating in this training can be seen from the success of producing quality content media after they held an independent exercise.